Control of the Half‐Skyrmion Hall Effect and Its Application to Adder–Subtractor. Issue 1 (19th November 2020) - Yang, Seungmo; Moon, Kyoung‐Woong; Kim, Changsoo; Kim, Duck‐Ho; Shin, Jeonghun; Hong, Jinpyo; Kim, Se Kwon; Hwang, Chanyong
Abstract: Skyrmions have attracted a great attention in spintronics because of their potential use as robust information carriers with distinctive protection. Though the realization of skyrmion‐based devices requires flexible control of a skyrmion motion, achieving such a skyrmion motion has been hampered by the skyrmion Hall effect (SkHE), which refers to the presence of a finite angle between a current and the skyrmion trajectory. Here, new insight for the precise control of half‐skyrmion motion is presented, including complete suppression of the SkHE by deforming the internal structure of skyrmions, which is experimentally achieved by external magnetic field to steer current‐driven half‐skyrmions in the desired direction. Furthermore, based on the unique advantages in half‐skyrmions, the potential of half‐skyrmions application beyond skyrmion‐based electronics is also demonstrated by presenting simple half‐skyrmion‐based addition/subtraction operation. The findings of controllability of 2D half‐skyrmion motion will provide new perspectives on utilization of topological solitons for device applications. Abstract : Precise control of a half‐skyrmion motion by deforming the internal structure of skyrmions is experimentally and theoretically demonstrated by utilizing external magnetic field. Furthermore, the distinct advantages of half‐skyrmions help to realize the potential of half‐skyrmions application beyond skyrmion‐based electronics by introducing addition/subtraction operation.